Un modelo tridimensional de la comunicación. Mediatización y la doble faz de la(s) realidad(es) social(es) - Andrés Vizer, Eduardo (Mediaciones Sociales, 2009)
The text discusses relations between information and communication, as mediations between structure and social processes. It proposes three dimensions in the process of communication, in relation to inditial and abductive processes of Peirce, as well as to categories of social analysis. The goal is to continue with the construction of a sociocommunicational framework for the research of social processes, following the ideas and propositions presented by Imre Lakatos for the development of research programs in sciences.